Consumption Level, and Nutritional Status of Schizophrenia Patient in Psychiatric Hospital Palu - . Irawati; Vera Uripi; Amini Nasoetion (Media Gizi dan Keluarga, 2001)
The objective of this research is to identify of availability, consumption, and waste of food; consumption level energy, protein, vitamin B1, B6 and B12; nutritional status schizophrenia patient; and analysis relationship between consumption level energy and protein with nutritional status schizophrenia patient.. This research was conducted in Psychiatric Hospital Palu, from February to April 2001. The total samples were 32 persons. Primary data were characteristic samples; kind and total food of availability, consumption, waste of food; and weigh/high body samples. The result of this research showed that kind of menu have composition were rice, side fish, vegetables, fruits and milk. Average of energy and protein consumption level each were 116,44% and 120,49% by Recomended Dietary Allowance (RDA) ang also thiamine (B1) 87,89%, but pyridoxines (B6) and cyan cobalt amine (B12) each 53,37% and 65% that lessthan of RDA. Mayority of the samples had good nutritional status (59,4%). Statistical analysis showed that consumption level of energy and protein has negative correlations with nutritional status